Architecting the Future U.S. Military Psychological Health Enterprise via Policy and Procedure Analysis. Issue 8 (1st August 2015) - Glover, Wiljeana J.; Plmanabhan, Jayaprasad; Rhodes, Donna; Nightingale, Deborah
ABSTRACT: Although researchers suggest that a systems approach is required to make meaningful advances in the U.S. psychological health care system for service members, limited research has considered such an approach. This research uses an enterprise architecting framework to identify the system's strengths and areas for opportunity as they relate to the Ecosystem, Stakeholders, Strategy, Process, Organization, Knowledge, Information, and Infrastructure. Codifying qualitative data from publicly available U.S. Defense Health Agency and U.S. Service Branch doctrine, policy guidance, and concepts of operations, our findings indicate that the psychological health care system is strongly process-oriented and mentions a variety of key stakeholders and their roles and responsibilities in the enterprise. Potential opportunities of improvement for the system include a stronger emphasis on the development and transfer of knowledge capabilities, and a stronger information-based infrastructure.